PENGARUH CAMEL TERHADAP HARGA SAHAM PADA BANK BUKU 4 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2019 - Holy Vilia; Fredella Colline (Business Administration Department - Universitas Katolik Parahyangan, 2021)
This study aims to determine the effect of CAMEL on stock prices at Bank Book 4 which is listed on the Indonesia Stock Exchange during 2016-2019 period. CAMEL ratio used in this study is CAR to measure capital aspects, NPL to measure assets quality aspect, NPM to measure management aspects, ROA to measure earnings aspects, and LDR to measure liquidity aspects. This study uses secondary data which includes 4 Bank Book 4 which are consistently in the category of Bank Book 4 from 2016 and Bank Book 4 which have a capital more than 100 trillion Rupiah. The data analysis technique that is going to be used is the multiple linear regression analysis. The result of hypothesis testing show that (1) CAR and NPL have no effect on stock prices, (2) NPM has a significant positive effect on stock prices, and (3) ROA and LDR have a significant negative effect on stock prices. Keywords: CAR, NPL, NPM, ROA, LDR, Stock Prices